The correlation between motorcycle riding duration with carpal tunnel syndrome among online ojek workers in Cimahi - Djajasasmita, Daswara; Dessy; Amalia, Farinez (ACTA Medical Health Sciences, 2024)
Carpal Tunnel Syndrome (CTS) is a neuropathy of the wrist caused by the compression within the carpal tunnel, which puts pressure on the median nerve. Riding a motorcycle combines the risk factors for CTS, including grip strength and repetitive movements. The flexibility of working hours has led to an increase in the number of online motorcycle taxi workers. This research uses a cross-sectional design, and the sample consisted of 82 individuals selected using purposive sampling technique. Research data were processed using the Chi-Square test. The duration of motorcycle riding, categorized as either ≥8 hours per day or <8 hours per day, is associated with a risk of developing CTS. The results of the questionnaire indicated that the most common CTS symptoms reported by ojek online workers was tingling, experienced by 70.73% of respondents, while the least reported symptom was difficulty grasping or using small objects, reported by 23.17% of participants. The Chi-Square analysis test revealed no significant difference in the incidence of CTS complaints between those who rode motorbike for ≥8 hours and thos who rode <8 hours per day among Ojek Online workers in Cimahi (pvalue 0.635). This insignificant difference may be due to other risk factors that influence the emergence of CTS in Ojek Online workers. DOI : 10.35990/amhs.v3n2.p68-74 REFERENCES Maher, A. B. (2016). Neurological assessment. International Journal of Orthopaedic and Trauma Nursing, 22, 44–53. https://doi.org/10.1016/j.ijotn.2016.01.002 Chairunnisa, S., Novianus, C., & Hidayati. (2021). Factors associated with carpal tunnel syndrome symptoms among online ojek communities in Tangerang City in 2021. JFKI, 1(2), 2807–8020. Sekarsari, D., Arum, D., & Amrin, F. (2017). The association between working hours, repetitive motion, and awkward hand postures with carpal tunnel syndrome symptoms among stone breaking workers. Journal of Public Health Student Research, 2(6), 1–9. Feng, B., Chen, K., Zhu, X., Ip, W. Y., Andersen, L., et al. (2021). Prevalence and risk factors of self-reported wrist and hand symptoms and clinically confirmed carpal tunnel syndrome among office workers in China: A cross-sectional study. BMC Public Health, 21(1), 1–10. Perţea, M., Ursu, S., Veliceasa, B., Grosu, O. M., Velenciuc, N., & Luncă, S. (2020). Value of ultrasonography in the diagnosis of carpal tunnel syndrome: A new ultrasonographic index in carpal tunnel syndrome diagnosis. Medicine (Baltimore), 99(29), e20903. Farahdhiya, F. A., Jayanti, S., & Ekawati. (2020). The association between duration, frequency, repetitive motion, and wrist posture with carpal tunnel syndrome in chamberstring orchestra violinists. Journal of Public Health, 8(5), 657–664. https://ejournal3.undip.ac.id/index.php/jkm/article/view/27947 Sylvano, L. (2021). Low back pain in online ojek drivers. Ebers Papyrus, 27(2), 42–49. Badan Pusat Statistik Indonesia. (2023). Indonesian Statistics 2023. Jakarta: Statistics Indonesia. Febrianti, W. (2020). Impact of online transportation service (Gojek) on employment expansion in Bandung City. Jurnal Ilmu Sosial dan Ilmu Politik, 6(1), 57. Ibnu, A., Djarot, S., & Mokhammad, R. (2020). Internet of things-based driving duration warning system to improve traffic safety. Journal of Transportation, 20(3), 191–200. Sylvano, L., & Novendy. (2021). The association between riding duration and low back pain symptoms in online ojek drivers. Ebers Papyrus, 27(2), 42–49. Datu, M. M. D., Kawatu, P. A. T., & Mandagi, C. K. F. (2019). The association between working hours and work fatigue in online ojek drivers of the Manguni Rider Online Community. Kesmas, 8(6), 601–607. Sari, M. F., & Novendy. (2022). Risk of suspected carpal tunnel syndrome in online ojek drivers. Jurnal Kesehatan Masyarakat, 4(2), 341–348. Nurdasari, A., & Ariasih, R. R. (2021). Factors associated with carpal tunnel syndrome (CTS) in online ojek drivers in South Tangerang City. Semesta Sehat Journal, 1(1), 10–17. Rukayah, S., & Lupita, L. (2020). Factors associated with work fatigue level in online ojek drivers in East Jakarta in 2019. Journal of Persada Husada Indonesia, 7(25), 31–37. Campbell, S., Greenwood, M., Prior, S., Shearer, T., Walkem, K., Young, S., et al. (2020). Purposive sampling: Complex or simple research case examples. Journal of Research in Nursing, 25(8), 652–661. Sarilar, A. C., & Gök, D. K. (2021). Value of the Boston Questionnaire in carpal tunnel syndrome. Neurological Sciences and Neurophysiology, 38(4), 245–249. Wibawa, R. A. K., & Agustin, I. W. (2019). Characteristics of motorcyclists involved in traffic accidents in Surabaya. Plan Urban Reg Environ, 8(0341), 295–302. Radinda, U. B. I. (2023). The effect of riding duration on musculoskeletal complaints among online ojek drivers in Bandung City. Universitas Muhammadiyah Surakarta. Fanny, A., & Aisyah. (2018). Factors influencing the occurrence of health complaints. Journal of Health Management of Soetomo Hospital Foundation, 4, 123–133. Setiawan, M. A. D., Made, N. W., & Muliarta, M. (2017). The association between wrist position while using a mouse and the risk of carpal tunnel syndrome in PT. X employees. Indonesian Physiotherapy Scientific Journal, 5(3), 40–43.